2018
DOI: 10.1111/crj.12903
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary functions in pseudoexfoliation syndrome

Abstract: These results suggest that there is decline in some pulmonary functions in pseudoexfoliation syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Literature review of positive risk factors for XFS in general [Tables 5 - 7 ][ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 ] and XFS in young subjects [ Table 8 ][ 82 83 84 85 86 87 88 89 90 91 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Literature review of positive risk factors for XFS in general [Tables 5 - 7 ][ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 ] and XFS in young subjects [ Table 8 ][ 82 83 84 85 86 87 88 89 90 91 …”
Section: Resultsmentioning
confidence: 99%
“…In the Lebanese cohort under investigation, XFS was associated with advanced age, glaucoma, habitual ocular rubbing, and longer time for cataract surgery. While advanced age [ Table 6 ],[ 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 ] glaucoma [ Table 5 ],[ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 ] and longer surgery duration[ 100 ] are well established risk factors for XFS [ Table 5 ],[ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 <...>…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 A strong positive association was found between self-reported asthma and PEX (p<0.001) in our study, with asthmatics having seven times greater odds of developing PEX than nonasthmatics. Batur et al, reported poorer pulmonary functions in individuals with PEX as compared to those without, 18 while Taylor et al found an increased risk of chronic obstructive pulmonary disease (COPD) diagnosis in individuals with PEX. 19 It was hypothesized that impaired elastogenesis associated with LOXL1 mutations in PEX may alter the repair processes in the lung, leading to pulmonary damage, especially after an insult such as cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%